PTR1: a reductase mediating salvage of oxidized pteridines and methotrexate resistance in the protozoan parasite Leishmania major. - Bello, A R (1994)
Trypanosomatid protozoans are pterin auxotrophs, a finding noted decades ago which heralded the discovery of key metabolic roles played by pteridines in eukaryotes. We have now identified the enzyme mediating unconjugated pteridine salvage in the human parasite Leishmania major, PTR1 (pteridine reductase 1, formerly hmtxr or ltdh). PTR1 is the gene in the amplified H region responsible for methotrexate (MTX) resistance, and belongs to a large family of oxidoreductases with diverse substrates and roles. We generated Leishmania lacking PTR1 by homologous gene targeting, and these ptr1- mutants required reduced biopterin (dihydro- or tetrahydrobiopterin) for growth. PTR1 purified from engineered Escherichia coli exhibited a MTX-sensitive, NADPH-dependent biopterin reductase activity. PTR1 showed good activity with folate and significant activity with dihydrofolate and dihydrobiopterin, but not with quinonoid dihydrobiopterin. PTR1 thus differs considerably from previously reported pteridine reductases of trypanosomatids and vertebrates. Pteridine reductase activity was diminished in ptr1- Leishmania and was elevated in transfected parasites bearing multiple copies of PTR1; correspondingly, ptr1- was MTX-hypersensitive whereas the multicopy transfectant was MTX-resistant. The concordance of the biochemical and genetic properties of PTR1 suggests that this is the primary enzyme mediating pteridine salvage. These findings suggest several possible mechanisms for PTR1-mediated MTX resistance and should aid in the design of rational chemotherapy.